2020
DOI: 10.1007/s00170-020-05986-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atomizing core on droplet dynamic behavior and machining characteristics under synergistically enhanced twin-fluid spray

Abstract: The droplet dynamic behavior of spraying during the manufacturing process affects tool life, cooling, and lubrication. A detailed understanding of droplet dynamic behavior is required to improve the surface quality while reducing the cutting fluid consumption. In this study, quantitative measurements for droplet diameter, number concentration, and axial velocity were carried out through a phase Doppler particle analyzer technique. The droplet characteristic spatial distributions of a standard twin-fluid nozzle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…To analyze the influence of various working parameters on the atomization flow field, the flow field distribution of the TFN was obtained using a multi-physics coupled acoustic-mechanics model. Previous studies have shown that the spray velocity has an important influence on both the particle size and distance, with a higher spray velocity favoring droplet breakup, resulting in a smaller overall droplet size and a longer spray distance [23]. Therefore, the water flow rate was selected as the variable for analyzing the effect of the water flow rate variation on the overall atomization flow field characteristics, and the effect of the water flow rate variation on the spray velocity was investigated.…”
Section: Multi-physics Coupled Acoustic-mechanics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the influence of various working parameters on the atomization flow field, the flow field distribution of the TFN was obtained using a multi-physics coupled acoustic-mechanics model. Previous studies have shown that the spray velocity has an important influence on both the particle size and distance, with a higher spray velocity favoring droplet breakup, resulting in a smaller overall droplet size and a longer spray distance [23]. Therefore, the water flow rate was selected as the variable for analyzing the effect of the water flow rate variation on the overall atomization flow field characteristics, and the effect of the water flow rate variation on the spray velocity was investigated.…”
Section: Multi-physics Coupled Acoustic-mechanics Analysismentioning
confidence: 99%
“…However, a multi-parameter and multi-objective analysis of the overall structure of a TFN is key to improving its efficiency. In our previous work, Chen et al [23,24] analyzed and compared the effects of self-excited vibrating cavity (SVC) on the spray performance of TFN using the phase Doppler method. Numerical analysis and comparative experiments on twin-fluid atomization nozzles under different parameter conditions were conducted, and the effects of different gas-liquid pressure ratios and structural parameters on the atomization performance were studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…3. First, the contact shape of a droplet is assumed to have an approximately spherical contact shape [16,17] with contact radius δ1 at the time that it reaches the metal surface (see Fig. 3(a)).…”
Section: Metal Surface Coloring Technologymentioning
confidence: 99%
“…As the most expensive hydraulic control component, electro-hydraulic servo control valve [50] has an impact on the performance of FCS. Chen et al [51] investigated that the factors influencing the property of FMU were the input current, servo fuel pressure, and direction of movement of fuel metering valve. Meanwhile, the effects of back pressure and other nonlinear factors on pressure difference across metering valve have been researched.…”
Section: Influence Factorsmentioning
confidence: 99%